2000
DOI: 10.1002/1097-4628(20000801)77:5<1096::aid-app17>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Fe(III) ions from dilute aqueous solutions by alginic acid‐enhanced ultrafiltration

Abstract: The removal of Fe(III) ions from aqueous solutions was studied using membrane filtration. A water-soluble polymer alginic acid (AA) was used to bind the metal ions, which was followed by batch ultrafiltration using poly(methyl methacrylatemethacrylic acid) membranes modified with poly(ethylene glycol) (PMMA-MA-PEG). The complexation behavior of AA and the effect pH on the rejection of iron were investigated. Maximum recovery of 87.13% was obtained when the filtration was carried out in the presence of AA at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…It has been shown that complexed uranium can be removed by UF with high retentions reported [14,15]. Considering that OM can be retained by UF to some extent [13] and influences the retention of metal ions [16,17], an investigation into the removal of uranium-OM complexes by UF would therefore be valuable. For the purpose of this study three types of OM, representative of compounds found in natural waters, were chosen as suitable for further exploration: HA, AA and TA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that complexed uranium can be removed by UF with high retentions reported [14,15]. Considering that OM can be retained by UF to some extent [13] and influences the retention of metal ions [16,17], an investigation into the removal of uranium-OM complexes by UF would therefore be valuable. For the purpose of this study three types of OM, representative of compounds found in natural waters, were chosen as suitable for further exploration: HA, AA and TA.…”
Section: Introductionmentioning
confidence: 99%
“…AA is known to be highly effective in the removal of metals from aqueous solutions [19,20,22], including uranium adsorption in wastewater treatment [23,24]. In fact the combination of AA with membrane processes has been found to lead to enhanced metal removal [16,17]. TA is a representative of plant polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, ultrafiltration has been classically employed to recover macromolecules, with molar masses of several thousands, from aqueous effluents. Thus, ultrafiltration membranes have been tested to recover metallic ions from aqueous solutions by adding macromolecules such as soluble polymers [10][11][12][13] and surfactants [14][15][16][17], which combine with the metals and enhance the separation. However, when dealing with these processes, a recovery step allowing the re-use of the surfactants or polymers is needed not only to decrease the operation costs associated with the additives but also to avoid discharges of organic material with the effluents containing the retained metals.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation, pH adjustment or polymer assisted filtration can lead to the precipitation or complexation of metals and subsequent removal of the precipitate by MF or UF [19,132,114,127,71,38].…”
Section: Solute-solute Interaction and Retention By Mf And Ufmentioning
confidence: 99%